Review of the Slender Geckos (Squamata: Gekkonidae: Hemiphyllodactylus) of the Cardamom Mountains of southwestern Cambodia, with descriptions of two new species and one country record - Neang, Thy; Samorn, Vireak; Hun, Seiha; Henson, Adam; Stuart, Bryan L. (Zootaxa, 2024)
The gekkonid lizard genus Hemiphyllodactylus contains small, secretive species that are often overlooked in their habitats. Recent molecular and morphological analyses have resulted in the descriptions of numerous new species of Hemiphyllodactylus in mainland Southeast Asia and southern China, many of which were historically hidden within the geographically widespread taxon H. yunnanensis (Boulenger, 1903). Little is known on species diversity and distributions of Hemiphyllodactylus in Cambodia, and all previous reports from the country have been limited to provisional identifications owing to collections containing only a single female or juvenile specimen. We report on new collections of Hemiphyllodactylus specimens from opposite ends of the Cardamom Mountain range in southwestern Cambodia. Morphological and molecular data support the hypothesis that these collections contain three distinct species, two of which are described as new species and one of which is assigned to the geographically widespread H. typus Bleeker, 1860 as a new country record for Cambodia. Hemiphyllodactylus bokor sp. nov. from Preah Monivong Bokor National Park in Kampot Province and Hemiphyllodactylus samkos sp. nov. from Phnom Samkos Wildlife Sanctuary in Pursat Province are related to species from adjacent areas in southern Vietnam, southern Laos, and southeastern Thailand, as well as a clade from India, but are readily differentiated in mitochondrial DNA and in having unique combinations of mensural and meristic morphological characters. Additional species diversity of Hemiphyllodactylus likely exists in Cambodia.